2002
DOI: 10.1016/s0022-474x(01)00047-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermal death kinetics and heating rate effects for fifth-instar Cydia pomonella (L.) (Lepidoptera: Tortricidae)

Abstract: Thermal death kinetic parameters of fifth-instar codling moths (Cydia pomonella (L.)) and the effect of three heating rates (11C min À1 , 101C min À1 , and 181C min À1 ) on larval mortality were determined by a heating block system. The insects were heated to four temperatures (461C, 481C, 501C, and 521C) held for predetermined periods followed by 24 h storage at 41C before mortality evaluation. Thermal death kinetics for fifth-instar codling moths followed a 0.5th order of kinetic reaction. Minimum time requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 30 publications
6
73
1
1
Order By: Relevance
“…The E a values for C. cephalonica were similar to those for S. oryzae (Yan et al 2014), fifth-instar Cy. pomonella (Wang et al 2002a), fifth-instar P. interpunctella (Johnson et al 2003), fifth-instar A. transitella (Wang et al 2002b), third-instar Ce. capitata (Gazit et al 2004), and Queensland fruit fly, Bactrocera tryoni eggs (Waddell et al 2000), larger than those Caribbean fruit fly, Anastrepha suspensa eggs (Moss and Chan 1993), but smaller than those for T. castaneum ) and Ce.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The E a values for C. cephalonica were similar to those for S. oryzae (Yan et al 2014), fifth-instar Cy. pomonella (Wang et al 2002a), fifth-instar P. interpunctella (Johnson et al 2003), fifth-instar A. transitella (Wang et al 2002b), third-instar Ce. capitata (Gazit et al 2004), and Queensland fruit fly, Bactrocera tryoni eggs (Waddell et al 2000), larger than those Caribbean fruit fly, Anastrepha suspensa eggs (Moss and Chan 1993), but smaller than those for T. castaneum ) and Ce.…”
Section: Resultsmentioning
confidence: 99%
“…This type of plot was used for thermal kinetics of Cy. pomonella by Wang et al (2002a). The z value (the temperature difference by which the mortality rate is altered by a factor of 10) was obtained from the TDT curve as described in details elsewhere .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result as in tabulated in Table 1. The effect of holding time is need significant consideration in designing the treatment to reach lethal temperature in order to obtain high mortality rate [24]. In term of heating rate and energy, it can be concluded that higher heating rate provide low mortality and it needs longer holding time to reach high mortality as low heating rate can provide [24].…”
Section: Experimental Findingsmentioning
confidence: 99%
“…The effect of holding time is need significant consideration in designing the treatment to reach lethal temperature in order to obtain high mortality rate [24]. In term of heating rate and energy, it can be concluded that higher heating rate provide low mortality and it needs longer holding time to reach high mortality as low heating rate can provide [24]. Siming Zhao reported complete disinfestation above energy consumption of 0.017 and 0.016 kWh/ks for adults and eggs respectively as the rice temperature from 55 to 62°C [23].…”
Section: Experimental Findingsmentioning
confidence: 99%